2005
DOI: 10.1017/s1047951105000910
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular noncompaction in a neonate with complex congenital heart disease

Abstract: Ventricular noncompaction is a rare unclassified cardiomyopathy occurring because of arrest of the normal intrauterine compaction of the loose luminal component of the ventricular myocardium. There is limited data regarding its diagnosis and outcome in children. It is recognised, however, that right ventricular involvement is extremely rare. We report a case in which only the right ventricular myocardium was noncompacted, a situation which led to heart failure soon after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…As a result, the 2DE diagnosis of HVM/NVM is often not made until patients had several 2DE. Ichida et al [12] found that the diagnosis was missed altogether in well over half of their study population of children. Similarly, the present case underwent an initial 2DE that did not confirm HVM/NVM.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As a result, the 2DE diagnosis of HVM/NVM is often not made until patients had several 2DE. Ichida et al [12] found that the diagnosis was missed altogether in well over half of their study population of children. Similarly, the present case underwent an initial 2DE that did not confirm HVM/NVM.…”
Section: Discussionmentioning
confidence: 91%
“…Although there is no established criteria for HVM/NVM in the right ventricle, right ventricle HVM/NVM has been reported in some cases [6][7][8][9][10][11][12] in whom the diagnosis of right ventricle HVM/NVM were pretty dependent on 2DE. The morphological assessment of the right ventricle is often difficult in adult patients by 2DE and 2DE image quality is operator dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases were associated with noncompaction of the left ventricular myocardium [7], while others were not [8]. The cases are extremely rare to be reported in which only the right ventricle was involved without evidence of left ventricular involvement in an adult subject [9].…”
Section: Introductionmentioning
confidence: 92%
“…Heart failure, thromboembolism and ventricular arrhythmias are the major clinical manifestations [3]. NCCM can be seen as an isolated malformation or associated with an obstructive lesion of the outflow tracts [4]. Hence, it is rare when NCCM is linked with ventricular septal defect and an atrial septal aneurysm.…”
mentioning
confidence: 99%